Shear bond strength of repairs in porcelain conditioned with laser - Pedrazzi, Hamilton; Garcia Takeuchi, Cristina Yoshie; Cioffi, Sabrina Spinelli [UNESP]; Galvao, Marilia Regalado [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Bezzon, Osvaldo Luiz (Wiley-Blackwell, 2012)
The aim of this study was to evaluate the shear bond strength of repairs in porcelain conditioned with laser. Sixty porcelain discs were made and six groups were formed (n = 10): G1: conditioning with laser with potency 760 mW; G2: conditioning with laser with potency 760 mW and application of 37% phosphoric acid for 15 s; G3: conditioning with laser with potency 900 mW; G4: conditioning with laser with potency 900 mW and application of 37% phosphoric acid for 15 s; G5: application of 37% phosphoric acid for 15 s (group control) and G6: application of 10% hydrofluoric acid for 2 min. The composite resin was insert of incremental layers at the porcelain surface aided with a metal matrix, and photoactivation for 20 s each increment. The specimens were submitted to a thermal cycling by 1000 cycles of 30 s in each bath with temperature between 5 and 55 degrees C. After the thermal cycling, specimens were submitted to the shear bond strength. The results were evaluated statistically through analysis of variance and Tukey's tests with 5% significance. The averages and standard deviation founded were: G1, 11.25 (+/- 3.10); G2, 12.32 (+/- 2.65); G3, 14.02 (+/- 2.38); G4, 13.44 (+/- 2,07); G5, 9.91 (-/+ 2,18); G6, 12.74 (+/- 2.67). The results showed that the femtosecond laser produced a shear bond strength of repairs in porcelain equal to the hydrofluoric acid and significantly superior to the use of phosphoric acid. Microsc. Res. Tech., 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: porcelain; bond strength; laser; composite resin